Association between TPH1 polymorphisms and the risk of suicide behavior: An updated meta-analysis of 18,398 individuals - Genis-Mendoza, Alma Delia; Hernández-Díaz, Yazmín; González-Castro, Thelma Beatriz; Tovilla-Zárate, Carlos Alfonso; Castillo-Avila, Rosa Giannina; López-Narváez, María Lilia; Ramos-Méndez, Miguel Ángel; Nicolini, Humberto (Frontiers in Psychiatry, 2022)
Objectives: we aimed to examine the association of TPH1 polymorphisms with the risk of suicide behavior (SB). Design: Systematic review and meta-analysis. Method: All relevant studies that evaluated the association between the A218C (rs1800532), A779C (rs1799913) and A6526G (rs4537731) polymorphisms and the susceptibility to SB published up to September 2021 were identified through a comprehensive systematic search in PubMed, Scopus, EBSCO and Science Direct electronic databases. The association between TPH1 gene polymorphisms and SB was evaluated using inherence models by odds ratio (OR) and 95% confidence interval (CI). Subgroup analyses, heterogeneity analyses, and publication bias were also tested in this meta-analysis. Results: The meta-analysis for TPH1 A218C revealed an increased risk of SB in the dominant model (OR = 1.11, 95%CI 1.01–1.22). We also observed a positive association in the allelic (OR=1.13, 95%CI 1.05-1.21), homozygous (OR=1.22, 95%CI 1.06-1.40), heterozygous (OR=1.21, 95%CI 1.08-1.37) and dominant (OR=1.21, 95%CI 1.09-1.34) inherence models with the suicide attempt. Additionally, in the heterozygous (OR = 0.84, 95%CI 0.73–0.97) and dominant (OR = 0.79, 95%CI 0.68–0.91) inherence models we detected an association with completed suicide. Based on ethnicity, an association of SB in the European population also was observed (OR = 1.29, 95%CI 1.12-1.51). However, for both A779C and A6526G polymorphisms we did not find evidence of an association with SB. Conclusion: This meta-analysis suggests that the A218C polymorphism of TPH1 gene could be a possible risk factor of SB. Future large-scale studies are required to analyze the molecular mechanisms by which affect the susceptibility of developing suicide behavior.